City in the American Hard-Boiled School of Detective Story - Diviš, Aleš (Univerzita Pardubice, 2014)
This bachelor thesis focuses on depiction of the city in the hard-boiled novels written by the most significant authors of this genre; Raymond Chandler and Dashiell Hammett, the representatives of the American hard-boiled school. The analysis is aimed at the role of the city as a literary place and its mysterious dark side which hides many secrets and symbolic features. With the use of the examples from their most popular works, the way both authors perceived and depicted the city within their stories was revealed.
Zobrazení města v detektivkách tzv. americké drsné školy
Keywords: hard-boiled school; Chandler, Raymond; Hammett, Dashiell; city; detectives; drsná škola; město; detektivové